(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
After years of medical research, it is clear that drug addiction is a complex multifactorial biological and behavioural disorder. Scientific advances have made it possible to develop treatments that help normalize the functioning of the brain of those affected and support them in changing their behaviour. Providing evidence-based treatments now helps millions of people regain control of their lives. It is the psychosocial work with these people that provides such methods that in cooperation with the addict, who must be prepared for this type of cooperation, can produce positive effects for him and the environment, including the family that is always most affected by the addictive problem. This paper deals with some of those methods, that is, systemic family therapy that would enable progress in the addict’s behaviour, his/her desire to change behaviour or treatments for relapse and prevention of relapse and recurrent behaviour. All this composition of psychosocial work, work through family therapies, and control over the addict enabled and assisted by official health and civic associations contribute to the formation of an overall strategy to help addicts and reduce the number of addicts in the country.